Characterization and performance of proton exchange membranes for direct methanol fuel cell: Blending of sulfonated poly(ether ether ketone) with charged surface modifying macromolecule - Mohd. Norddin, M. N. A.; Ismail, Ahmad Fauzi; Rana, D.; Matsuura, T.; Mustafa, A.; Tabe-Mohammadi, A. (Elsevier B.V., 2008)
Modification of sulfonated poly(ether ether ketone) (SPEEK) membrane was attempted by blending charged surface modifying macromolecule (cSMM). The modified membrane was tested for direct methanol fuel cell (DMFC) application; i.e. a SPEEK/cSMM blend membrane was compared to a SPEEK membrane and a Nafion 112 membrane for the thermal and mechanical stability, methanol permeability, and proton conductivity. Thermal and mechanical stability of the blended membrane were slightly reduced from the SPEEK membrane but still higher than the Nafion 112 membrane. The blend membrane was found to be promising for DMFC applications because of its lower methanol diffusivity (2.75×10−7 cm2 s−1) and higher proton conductivity (6.4×10−3 Scm−1), than the SPEEK membrane. A plausible explanation was given for the favorable effect of cSMM blending